Dino poet - Angleberger, Tom (New York, NY : Abrams Fanfare, 2025)
Get writing or get eaten! Dino Poet is on a mission: to write the first great poem--ever! His lunch, a prehistoric frog, is also on a mission: to not get eaten! So when Frog tells Dino Poet that his poems stink, he decides lunch can wait... for now. The two set off into the wide, wild world, chasing life! Chasing poetry! Until a T-Rex starts chasing them. From the incomparable mind of New York Times bestselling author Tom Angleberger, Dino Poet kicks off a hilarious graphic-novel series that is a rollicking romp through the land of the dinosaurs and a celebration of the poets that live in all of us.
K-12.
Keywords: Dinosaurs -- Comic books, strips, etc; Frogs -- Comic books, strips, etc; Poetry; Graphic novels; Humorous comics; Comics (Graphic works); Poetry